Rheological, mechanical and physical properties of poly-lactic acid (PLA)/ hydroxyapatites (HA) composites prepared by an injection moulding process / Afeeqa Puteri Marzuki … [et al.] - Marzuki, Afeeqa Puteri; Mohd Salleh, Farrahshaida; Rosli, Muhammad Nazri Shah; Tharazi, Izdihar; Abdullah, Abdul Hakim; Abdul Halim, Nurul Hayati (Universiti Teknologi MARA, 2022)
Poly-lactic acid (PLA) is an attractive biopolymer where it is biocompatible with respect to biomedical applications. Hydroxyapatite (HA) ceramics have been broadly practiced as bone substitutes because of their chemical composition close to the mineral phase of bone. Indirectly, the combination of PLA and HA would be a suitable biomaterial candidate for implant and bone repair applications. In this study, the feedstock composition of PLA/HA has been investigated to obtain good rheological properties before undergoing an injection moulding process. The process begins with mixing the specific powder loadings of 60 wt.% PLA/ 40 wt.% HA at 30 rpm of rotating speed and 180 oC of mixing temperature. Then, the feedstock is evaluated using a capillary rheometer at three different temperatures, 140 oC, 150 oC, and 160 oC. Feedstock exhibiting pseudoplastic flow (n<1) is chosen for the injection moulding process. The result shows injected moulded part successfully produced at barrel and nozzle temperature of 160 oC, mould temperature of 37 oC and injection pressure of 0.7 MPa. The injected parts were characterized for physical and mechanical properties. The PLA/HA specimen density is 1.564 ± 0.02 g/cm3. The Young’s Modulus of the tensile is 1.82 ± 0.5 GPa within the range of human bone, 1.15 to 5.44 GPa.